Flow stability, convective heat transfer and chemical reactions in ammonothermal autoclaves—insights by in situ measurements of fluid temperatures - Schimmel, Saskia; Kobelt, Ines; Heinlein, Lukas; Kimmel, Anna-Carina; Steigerwald, Thomas; Schlücker, Eberhard; Wellmann, Peter (Crystals, 2020)
A variety of functional nitride materials, including the important wide bandgap semiconductor GaN, can be crystallized in exceptionally good structural quality by the ammonothermal method. However, the further development of this method is hindered by a lack of access to internal process parameters including fluid temperatures, flow stability and reaction kinetics. Internal temperature measurements are thus introduced as a tool for in situ monitoring of fluid flow stability in ammonothermal reactors as well as chemical reactions associated with enthalpy changes. The temperature change of an internal thermocouple is studied numerically in order to estimate possible errors due to heat conduction along thermocouples as well as due to their heat capacity. Results from otherwise identical experiments conducted with air at ambient pressure and ammonothermal reaction medium, respectively, are compared. The comparison indicates that internal temperature distributions during ammonothermal growth of GaN cannot be determined by measurements using ambient pressure air instead of supercritical ammonia. Even an approximate determination is not feasible, given that the internal temperature gradients differ by a factor of seven, and that the Grashof-and Rayleigh numbers differ by approximately four orders of magnitude. Most importantly, convective heat transfer by supercritical ammonia is found to greatly influence the temperature distribution inside the reaction chamber and its walls, suggesting that it probably needs to be taken into account in numerical simulations of the global thermal field of ammonothermal reactors.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Ammonothermal; Bulk crystal growth; Convective heat transfer; Fluid flow; GaN; In situ monitoring; Natural convection; Reaction monitoring; Solvothermal

In Situ Monitoring Technologies as Prospective Validation Tools for Numerical Simulations of Ammonothermal Crystal Growth - Schimmel, Saskia; Salamon, Michael; Tomida, Daisuke; Kobelt, Ines; Heinlein, Lukas; Kimmel, Anna-Carina; Steigerwald, Thomas; Ishiguro, Tohru; Honda, Yoshio; Chichibu, Shigefusa F.; Amano, Hiroshi; Schlücker, Eberhard; et al. (7th European Conference on Crystal Growth, 2022)